Botulinum Toxin as Monotherapy in Symptomatic Trigeminal Neuralgia. Issue 6 (17th March 2016) - Lunde, Hanne Marie Bøe; Torkildsen, Øivind; Bø, Lars; Bertelsen, Anne Kjørsvik
Abstract : Background: Trigeminal neuralgia (TN) is one of the most agonizing facial pain disorders that humans endure. Studies on onabotulinum toxin A (BTX‐A) treatment for TN are limited, but promising with respect to TN of no identifiable cause. We aimed to investigate the efficiency and safety of BTX‐A treatment in a 60‐year‐old male with diabetes mellitus who in March 2013 presented with TN caused by an exostosis in Meckel's cave. Methods: The patient was medically treatment refractory due to insufficient pain relief and adverse events of hyperglycemia, and surgery was declined due to complex anatomy. As a last resort, BTX‐A was injected into the pain trigger zones of the trigeminal nerve (V5). Results: Complete analgesia was reported 2 weeks after BTX‐A injection. Pain medications were discontinued and laboratory values returned to acceptable levels. Regular BTX‐A treatment during the next 28 months showed sustained analgesic effect. Conclusions: BTX‐A has an excellent safety profile and may be efficient for patients with symptomatic TN not suited for conventional therapies.